ANALISIS PENETAPAN PROFIT MARGIN PADA PRODUK PEMBIAYAAN MURABAHAH (STUDI KASUS PADA BMT-MMU SIDOGIRI, PASURUAN) - PRAMUDYA R., ANGGA Pramudya (Jurnal Akuntansi AKUNESA, 2013)
The purpose of the research on BMT-MMU is to determine (1) Procedures murabaha(2) The murabaha margin. Methods of research using descriptive methods, sources of data inthis study there are two sources of primary data and secondary data sources. Financingprocedures in BMT-MMU financing system adopted in accordance with shariah guidelines,effective and efficient with the provisions previously a partner opened a savings account.Murabaha margin percentage margin calculation formula and the selling price.Keyword: Margin, financing, Murabahah.